1977
DOI: 10.1073/pnas.74.4.1358
|View full text |Cite
|
Sign up to set email alerts
|

Rat liver preproalbumin: in vitro synthesis and partial amino acid sequence.

Abstract: Rat liver poly(A-containing RNA greatly stimulated incorporation of radioactive amino acids into protein when added to a wheat germ in vitro translation system. Approximately 7% of the labeled synthetic product was precipitated following indirect immunoprecipitation with antisera to rat serum albumin. Analysis of this material, and of the cyanogen bromide fragments derived from it, by sodium dodecyl sulfate/polyacrylamide gel electrophoresis revealed that it contained an NH2-terminal extension of about 2500 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
1

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 35 publications
4
56
0
1
Order By: Relevance
“…On some occasions we have found that labeled cell-free product migrates in the trailing region slightly behind the major portion of serum albumin stained with Coomassie Blue. This cell-free product may represents a precursor to rat serum albumin as reported by Strauss et al (40). Taylor and Tse (22) have reported the isolation of albumin mRNA by using other techniques.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…On some occasions we have found that labeled cell-free product migrates in the trailing region slightly behind the major portion of serum albumin stained with Coomassie Blue. This cell-free product may represents a precursor to rat serum albumin as reported by Strauss et al (40). Taylor and Tse (22) have reported the isolation of albumin mRNA by using other techniques.…”
Section: Resultsmentioning
confidence: 97%
“…For oligo(dT)-cellulose chromatography, the RNA was dissolved in 10 mM Tris-HCl (pH 7.4)/0.5% NaDodSO4 and heated to 650 for 5 min. The RNA solution was then cooled rapidly by the addition of an equal volume of 1 M NaCl (40). This material was placed over a 3-ml packed oligo(dT)-cellulose column.…”
Section: Methodsmentioning
confidence: 99%
“…Messenger RNAs that encode for secretory proteins direct the synthesis in various cell-free systems of precursor forms (designated pre) containing an extra N-terminal sequence of about 25 amino acids [1][2][3][4][5][6][7][8]. It has been suggested that the extra protein portion plays a role in mediating the formation of membranebound ribosomal complexes [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous secretory proteins have been shown to be synthesized as presecretory proteins containing an amino-terminal extension of 15-30 amino acid residues (signal peptide) when their mRNAs are translated in a cell-free system in the absence of microsomal membranes (1)(2)(3)(4)(5)(6)(7)(8)(9). In the signal hypothesis (10), it has been proposed that the signal peptide of a nascent presecretory protein nucleates the formation of a functional ribosome-membrane junction which, in turn, provides the topological condition for a cotranslational transfer of the nascent secretory protein across the rough endoplasmic reticulum (RER) membrane into the intracisternal space of the RER.…”
mentioning
confidence: 99%